About their own sets of superlinear mappings - Makazhanova Т.Kh.; Mukanov А.А. (Bulletin of the Karaganda University. Mathematics Series, 2016)
In this paper we obtain a theorem of existence of its own sets the superlinear point - to - set mappings defined on cones orderly normed spaces. Suﬃcient conditionsare the continuity of the mapping on the set of convex weak compacta of the cone and the limitations on the track unit ball of the space.